Barbados. Swan Street (looking East). Bridgetown. - Cooper, W. G. (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2022)
This is an aerial view of Swan Street, Bridgetown. A busy street scene with many people, dressed in the fashion of the day, going about their business. The women are dressed in long dresses and hats, the men are wearing suits. Vendors are seen plying their trade at the side of the street, some with their ware atop their heads. Commercial businesses line both sides of the street, the most recognizable signage being that of “Hart and Company: The Tailor’s Warehouse” at #31. The most visible architectural features of the buildings are the roof work, the doors, windows and balconies. Also on the front of the postcard : No. 24 W.G. Cooper, Copyright. B Series of 24. This is a divided back postcard. Back of the postcard: Thursday, March 14 – 07: All were shopping together for a while and then the sun left us, and Mrs. Falls, Karolyn, and I wandered in, out, place after place for a good while but could not find very much. HNED £35 (Handwritten in Pencil)
Landscape; Black & white; 3 ½” x 5½ ”
Keywords: Aerial Views; Roofs; Windows; Architecture; Buildings; Cityscapes; City and town life; Cities and towns; Commercial streets; Business districts; Business enterprises; Architectural elements; Clothing and dress; People; Street vendors; Swan Street; Hawkers